2021
DOI: 10.1002/cbdv.202100396
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and α‐Glucosidase Inhibitory Xanthones from Garcinia mckeaniana Leaves and Molecular Docking Study

Abstract: A new racemic xanthone, garmckeanin A (1), and eight known analogs 2–9 were isolated from the ethyl acetate (AcOEt) extract of the Vietnamese Garcinia mckeaniana leaves. Their structures were determined by MS and NMR spectral analyses and compared with the literature. The AcOEt extract showed good cytotoxicity against cancer cell lines KB, Lu, Hep‐G2 and MCF7, with IC50 values of 5.40–8.76 μg/mL, and it also possessed α‐glucosidase inhibitory activity, with an IC50 value of 9.17 μg/mL. Garmckeanin A (1) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Thi et al (Nguyen et al, 2021) found that GE exhibited strong inhibitory effects in the proliferation of MDA‐MB‐231 breast cancer cells with an IC 50 value of 8.95 μM, which is lower than that of cisplatin (IC 50 = 26.5 μM), a widely used chemotherapeutic agent for breast cancer treatment (Li, Xu, & Peng, 2022). Ha et al (Thi Thu et al, 2021) reported that GE exhibited strong cytotoxic activity against MCF‐7 cells, with an IC 50 of 8.07 μM. In accordance with previous studies, we confirmed the cytotoxicity of GE against MDA‐MB‐231, MCF‐7, and 4T1 breast cancer cells with IC 50 values of 0.68, 2.27, and 1.21 μM, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Thi et al (Nguyen et al, 2021) found that GE exhibited strong inhibitory effects in the proliferation of MDA‐MB‐231 breast cancer cells with an IC 50 value of 8.95 μM, which is lower than that of cisplatin (IC 50 = 26.5 μM), a widely used chemotherapeutic agent for breast cancer treatment (Li, Xu, & Peng, 2022). Ha et al (Thi Thu et al, 2021) reported that GE exhibited strong cytotoxic activity against MCF‐7 cells, with an IC 50 of 8.07 μM. In accordance with previous studies, we confirmed the cytotoxicity of GE against MDA‐MB‐231, MCF‐7, and 4T1 breast cancer cells with IC 50 values of 0.68, 2.27, and 1.21 μM, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Cytotoxic assay for the EtOAc extracts of DH1‐DH3 was carried out using our previous reports [53–56] . Briefly, cancer cells were cultured in DMEM, which includes L‐glutamine (2 mM), NaHCO 3 (1.5 g/L), glucose (4.5 g/L), HEPES (10 mM), sodium pyruvate (1 mM), and FBS (Fetal Bovine Serum, 10 %).…”
Section: Methodsmentioning
confidence: 99%
“…Three EtOAc samples were further subjected to α ‐glucosidase inhibitory and anti‐inflammatory experiments. In α‐glucosidase inhibitory assay, samples were dissolved by DMSO to yield final concentrations of 256, 64, 16, 4, and 1 μg/mL [35,36,53] . In a 96‐well plate, a mixture, consisting of 10 μL of each tested sample at various concentrations, phosphate buffer (40 μL, pH 6.8), α ‐glucosidase (0.4 U/mL, 25 μL), was incubated for 15 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Garcinia mckeaniana , also called Xen mu, is a common plant that is widespread in the tropical secondary forests of Sapa town and Son La province of Vietnam in particular. So far, a few studies have been conducted on the phytochemistry and biological properties of Garcinia mckeaniana ( Auranwiwat et al, 2016 ; Ha et al, 2021 ; Nguyen et al, 2021 ; Thi Thu et al, 2021 ). The biphenyl ( 19 ) was denominated as mckeaninabiphenyl and had been synthesized previously ( Sato and Mikawa, 1960 ).…”
Section: Diverse Biphenyls From Clusiaceae and Their Bioactivitymentioning
confidence: 99%